Vibrotactile Presentation of Musical Notes to the Glabrous Skin for Adults with Normal Hearing or a Hearing Impairment: Thresholds, Dynamic Range and High-Frequency Perception. - Carl Hopkins; Saúl Maté-Cid; Robert Fulford; Gary Seiffert; Jane Ginsborg (PLoS ONE)
Presentation of music as vibration to the skin has the potential to facilitate interaction between musicians with hearing impairments and other musicians during group performance. Vibrotactile thresholds have been determined to assess the potential for vibrotactile presentation of music to the glabrous skin of the fingertip, forefoot and heel. No significant differences were found between the thresholds for sinusoids representing notes between C1 and C6 when presented to the fingertip of participants with normal hearing and with a severe or profound hearing loss. For participants with normal hearing, thresholds for notes between C1 and C6 showed the characteristic U-shape curve for the fingertip, but not for the forefoot and heel. Compared to the fingertip, the forefoot had lower thresholds between C1 and C3, and the heel had lower thresholds between C1 and G2; this is attributed to spatial summation from the Pacinian receptors over the larger contactor area used for the forefoot and heel. Participants with normal hearing assessed the perception of high-frequency vibration using 1s sinusoids presented to the fingertip and were found to be more aware of transient vibration at the beginning and/or end of notes between G4 and C6 when stimuli were presented 10dB above threshold, rather than at threshold. An average of 94% of these participants reported feeling continuous vibration between G4 and G5 with stimuli presented 10dB above threshold. Based on the experimental findings and consideration of health effects relating to vibration exposure, a suitable range of notes for vibrotactile presentation of music is identified as being from C1 to G5. This is more limited than for human hearing but the fundamental frequencies of the human voice, and the notes played by many instruments, lie within it. However, the dynamic range might require compression to avoid the negative effects of amplitude on pitch perception.